A bean sprout-like cobalt selenium phosphorus nanosheet-composed anode toward fast and high sodium-ion storage. Issue 32 (31st March 2023) - Zhang, Heng; Bai, Youcun; Liu, Jiawang; Li, Juan; Zou, Zhuo; Song, Wenliang; Sun, Wei; Li, Chang Ming
Abstract : This work vividly demonstrates the rational design of a coblat selenophosphide anode as an effective strategy to accomplish fast and high sodium-ion storage. Abstract : A metal–organic framework (MOF) is used to thermally grow cobalt selenophosphide (CoSeP) nanoparticles on an N-doped 2-dimensional carbon matrix (CoSeP@N-C), resulting in an assembled unique 3-dimensional bean sprout-like nanosheet composite with massive defects as an advanced anode material of sodium ion batteries. The results indicate that the massive defects in the CoSeP@N-C sprout-like 3-D structure can offer high density of reaction sites and well accommodate the volume change during the sodiation/desodiation process, while rendering abundant channels for rapid transport of sodium ions, thereby synergistically making the CoSeP@N-C anode much more reversible for the sodium ion storage process and producing higher rate performance than those of CoP2 and CoSe2 @N-C. The ex situ X-ray diffraction, ex situ Raman and ex situ TEM analyses further confirm the mechanism of sodium storage intercalation and transformation in CoSeP@N-C. This work vividly demonstrates a rational design of metal selenophosphide anodes as an effective strategy to accomplish fast and high sodium-ion storage.